Measurements of the Sound Absorption Coefficient of Auditorium Seats for Various Geometries of the Samples - RUBACHA, Jarosław; PILCH, Adam; ZASTAWNIK, Marcin (Archives of Acoustics, 2012)
This paper presents the results of measurements of the sound absorption coefficient of auditorium seats carried out in the laboratory using two methods. In the first one, small blocks of seats in various arrangements were studied in a reverberation chamber to determine the absorption coefficient of an auditorium of infinite dimensions. The results were compared to the values of the absorption coefficient measured using the second method, which involved samples enclosed within a frame screening the side surfaces of other auditorium blocks. The results of both methods allowed for the assessment of the sound absorption coefficient of an auditorium of any dimensions while taking into account the sound absorption by the side surfaces. The method developed by the authors will simplify the currently known measurement procedures.